Methodology for designing intrahospital transportation of patients with suspected infectious disease that limits infection spread risk in China - Guo, Yuan; Li, Yanchu; Wang, Yanjun; Liang, Pengpeng; He, Xiaoli; Yu, Bingjie; Chen, Fangyu; Zeng, Qianhui (Frontiers in Public Health, 2023)
Aims The transport of patients suspected of having COVID-19 requires careful consideration. Using paths selected at random and not accounting for person flow along the path are risk factors for infection spread. Intrahospital transportation (IHT) protocols and guidelines should be used to help reduce the risk of secondary virus transmission during transport. This study aimed to propose optimal IHT for patients with an infectious disease presenting in an out-patient area. Design The map of a West China Hospital was used. We also used field investigation findings and simulated person flow to establish pathway length and transportation time. We identified three optimum pathways and estimated safety boundary marks, including a patient transportation border (PTB) and safety transportation border (STB). Finally, IHT, PTB, and STP formed a virtual transport pipeline (VTP) and a traceable IHT management system, which can generate a virtual isolation space. Results The three pathways met efficiency, accessibility, and by-stander flow criteria. No facility characteristic modification was required. Conclusions Using virtual models to identify pathways through out-patient hospital areas may help reduce the risk of infection spread.